Tales of the neighborhood : Jewish narrative dialogues in late antiquity - Hasan-Rokem, Galit (Taubman lectures in Jewish studies ;, 2003)
Showing that religion is shaped to some extent by the ordinary events of everyday life, this text focuses on the 'neighbourhood' of the Galilee, bringing to life the riddles parables and folktales passed down in Rabbinic stories from the first half of the first millennium of the Common Era.